Discovery of prosimian and afrotherian foamy viruses and potential cross species transmissions amidst stable and ancient mammalian co-evolution. - Katzourakis, A; Aiewsakun, P; Jia, H; Wolfe, N; LeBreton, M; Yoder, A; Switzer, WM (BioMed Central, 2014)
BACKGROUND: Foamy viruses (FVs) are a unique subfamily of retroviruses that are widely distributed in mammals. Owing to the availability of sequences from diverse mammals coupled with their pattern of codivergence with their hosts, FVs have one of the best-understood viral evolutionary histories ever documented, estimated to have an ancient origin. Nonetheless, our knowledge of some parts of FV evolution, notably that of prosimian and afrotherian FVs, is far from complete due to the lack of sequence data. RESULTS: Here, we report the complete genome of the first extant prosimian FV (PSFV) isolated from a lorisiforme galago (PSFVgal), and a novel partial endogenous viral element with high sequence similarity to FVs, present in the afrotherian Cape golden mole genome (ChrEFV). We also further characterize a previously discovered endogenous PSFV present in the aye-aye genome (PSFVaye). Using phylogenetic methods and available FV sequence data, we show a deep divergence and stable co-evolution of FVs in eutherian mammals over 100 million years. Nonetheless, we found that the evolutionary histories of bat, aye-aye, and New World monkey FVs conflict with the evolutionary histories of their hosts. By combining sequence analysis and biogeographical knowledge, we propose explanations for these mismatches in FV-host evolutionary history. CONCLUSION: Our discovery of ChrEFV has expanded the FV host range to cover the whole eutherian clade, and our evolutionary analyses suggest a stable mammalian FV-host co-speciation pattern which extends as deep as the exafroplacentalian basal diversification. Nonetheless, two possible cases of host switching were observed. One was among New World monkey FVs, and the other involves PSFVaye and a bat FV which may involve cross-species transmission at the level of mammalian orders. Our results highlight the value of integrating multiple sources of information to elucidate the evolutionary history of viruses, including continental and geographical histories, ancestral host locations, in addition to the natural history of host and virus.